13 Myocardial fibrosis entropy is associated with life-threatening arrhythmia in non-ischaemic cardiomyopathy. (28th January 2023) - Hammersley, Daniel J; Zaidi, Hassan A; Jones, Richard E; Hatipoglu, Suzan; Androulakis, Emmanuel; Mach, Lukas; Lota, Amrit S; Tayal, Upasana; Khalique, Zohya; Marvao, Antonio De; Baruah, Resham; Guha, Kaushik; et al.
Abstract : Introduction: Greater precision is required for arrhythmic risk stratification of patients with non-ischaemic cardiomyopathy (NICM). We sought to evaluate whether fibrosis entropy, a measure of scar texture heterogeneity derived from late gadolinium enhancement cardiovascular magnetic resonance (LGE-CMR), had incremental utility to fibrosis presence for arrhythmic risk prediction in NICM. Materials and Methods: Prospective observational cohort study of consecutive patients with NICM and myocardial fibrosis detected by LGE-CMR. Entropy (computed as standard Shannon Entropy) was calculated for core fibrosis, gray zone (GZ), and combined core and GZ fibrosis. Core fibrosis was classified using full width half maximum method and GZ fibrosis as regions with ≥35% but <50% maximum signal intensity. Patients were followed up for life-threatening arrhythmia [LTA] (sudden cardiac death, aborted sudden cardiac death or sustained ventricular tachycardia). Results: Of 292 patientswith NICM and mid-wall/subepicardial fibrosis, 38 patients (13.0%) experienced LTA over median follow-up of 6.3 years (IQR 4.6–9.1years). Core fibrosis entropy (HR 1.63, 95%CI 1.15–2.30, p=0.006), GZ fibrosis entropy (HR 1.68, 95%CI 1.16–2.44, p=0.006) and combined fibrosis entropy (HR 1.65, 95%CI 1.11–2.44, p=0.013) were independently associated with LTA after adjustment for variables used to guide ICD implantation (LVEF<35% and NYHA class >1) and remained associated in multivariable models accounting separately for core and GZ fibrosis mass. The addition of core fibrosis entropy, GZ fibrosis entropy and combined fibrosis entropy to a baseline clinical model improved the C-statistic from 0.49 to 0.63, 0.62 and 0.63 respectively. LVEF<35% was not associated with LTA (HR 1.45, 95%CI 0.77–2.74, p=0.25). Discussion: Fibrosis entropy was associated with LTA in patients with NICM and mid-wall/subepicardial fibrosis. This association was independent of benchmark variables used in clinical practice and the addition of fibrosis entropy to arrhythmic risk models enhanced their predictive power. The comparable increment in C-statistic for core and GZ fibrosis entropy indicates equivalent effect on arrhythmic risk from each. The lack of association between LVEF and LTA highlights the inadequacy of the current paradigm for determining primary prevention ICD candidacy and provides further impetus for transition towards methods directly evaluating underlying arrhythmic substrate. Conclusion: Fibrosis entropy has incremental utility to fibrosis presence in arrhythmic risk prediction of patients with NICM. Acknowledgements: We thank the Royal Brompton and Harefield Cardiovascular Research Centre nurses and support staff, led by Ms Geraldine Sloane.